Current State and History of the Measurement of Implicit Attitudes - Hideya Kitamura (Maketingu Janaru)
Implicit attitudes in the field of social psychology are reviewed and explained. Distinguishing between implicit and explicit measures and how implicit measurements emerged are described. Attitude strength and accessibility were introduced through the research of Fazio et al., which served as a theoretical precursor to the theory of implicit attitudes. Implicit attitudes measured by the Implicit Association Test (IAT) developed by Greenwald et al. are influenced by environmental and situational factors. The author discussed the characteristics found in the IAT, including the author’s empirical evidence, and found that implicit attitudes can change in the short term. Finally, criticisms of the IAT and other points to keep in mind are discussed.